Vivienda de alta densidad - Vargas Yerovi, Hugo Giovanny (2016)
Inhabit a space involves several social components, space is rarely unique to an individual and less a dense and globalized system as it is in the currently inhabit. The house is part of humanity since the beginning, why requires a specific implementation for each site where it is located; every individual, family or community member establishes an identity which characterizes the space it inhabits. Expose and generate a sense of identity and space appropriation is a goal that must be raised by those doing residential projects, as this is the base of an orderly, efficient oriented and just society. Establish housing as a small component of a large urban system can be understood as the base of social relations and cultural exchange because its approach should be based on the environment, generate city, dynamism and communication between those who can be founded in that system, which by its physical, spatial and social characteristics arises under a concept of proximity in order to function as the distances are the first limiting the individual can find in the urban space. This statement implies not wasting space, a habit that the current urban development has relegated as a mere theory and ultimately, have been the way how the world has grown until consume the farthest corners of the planet.